Teasing and harassment : the frames and scripts approach for teachers and parents - Hoover, John H.; Olsen, Glenn W. (Glenn William). (Bloomington, Ind. : Solution Tree, 2001)
Provides concrete skills that parents and teachers can learn to help counter and prevent verbal aggression.
'Solutions'--Cover.
Includes bibliographical references (p. 121-125).
Keywords: Teasing; Harassment; Interpersonal relations